PENGARUH PERSEPSI KONSEP IMUNISASI DALAM AGAMA ISLAM TERHADAP PEMBERIAN IMUNISASI DI WILAYAH KERJA PUSKESMAS SERANG KOTA TAHUN 2018 - M. Mansur Halwani; Nur Avenzoar; Evi Avicenna Agustin (Poltekkes 'Aisyiyah Banten, 2020)
Immunization aims to reduce the number of sufferers of a disease that is very dangerous to health and can even cause death in the sufferer. Some diseases that can be avoided by immunization are hepatitis B, measles, polio, diphtheria, tetanus, whooping cough, mumps, chicken pox, tuberculosis, and so on. The purpose of immunization is in line with the teachings of Islam which obliges someone to maintain health, because maintaining health is the first basis and one of the preventive measures from disease. The higher the level of individual public awareness of health, the higher the attention to preventive action against disease can be done to a very large degree The research objective was to determine the concept or theory of immunization in Islam and its laws and practices. The author focuses research on library research (library research) and tries to study about immunization in Islam, the type of research used is quantitative research. The study population was the number of toddlers until August 2018 as many as 213 people with a sample of 100 respondents. Results of the study There were 15% of children under five who were not given basic immunization in the Serang Kota Community Health Center. there are 18% bad perceptions about the concept of immunization in Islam towards the provision of immunization in the Serang Kota Health Center Work Area, There is a relationship between Perceptions of the Concept of Immunization in Islam and the Giving of Immunization in the Serang City Health Center Keja Area Midwives and other health workers as implementers of communicable disease prevention programs are able to collaborate with experts in the field of religion and public health behavior so that it is easier to approach and change the views of religious and community leaders in areas with low immunization coverage.